ANALYSIS OF THE GENDER DEVELOPMENT INDEX IN EAST JAVA REGENCY/CITY IN 2017-2019 - Farida Rahmawati; Afrilia Nur Aini; Elmira Mufliha Camila (Riset Ekonomi Pembangunan, 2021)
This research aims to analyze the effect of government spending on education and health, economic growth, poverty levels, and Labor Force Participation Rate (LFPR) on the gender development index of regency/cities in East Java in 2017-2019. This research uses a quantitative approach and panel data regression using a fixed effect model, as the technical data analysis. The results showed that the government expenditure variables for education and health had a positive and insignificant effect on the gender development index in East Java. The economic growth variable has a negative and significant effect on the gender development index in East Java. The poverty rate variable has a negative and significant effect on the gender development index of regency/cities in East Java. While, the variable of Labor Force Participation Rate (LFPR) has positive and insignificant influence towards gender development index of regency/city in East Java.